Illocutionary Acts Produced by the Main Characters in Khaled Hosseini's "A Thousand Splendid Suns" - Sarah Sumponogati (Dinamika Bahasa dan Budaya, 2015)
This study is aimed at finding illocutionary acts and the speech function of the main characters in Khaled Hosseini's novel "A Thousand Splendid Suns", particularly the part one of the novel. This research is designed in descriptive qualitative. The procedure of analyzing the utterances is based on the criteria proposed by Searle (1997) and Schiffrin (1994). The results show that the utterances produced by the main characters in part one of the novel are mostly using directive, followed by commissives and representative, but rarely with expressives. There is no declarative at all in the part one of the novel. Key words: Novel, utterance, illocutionary act, speech function